High post-annealing stability for perpendicular [Co/Ni]n multilayers by preventing interfacial diffusion. (6th April 2016) - Li, Xu-Jing; Jiang, Shao-Long; Zhang, Jing-Yan; Han, Gang; Liu, Qian-Qian; Liu, Yi-Wei; Wang, Dong-Wei; Feng, Chun; Li, Ming-Hua; Yu, Guang-Hua
Abstract: This paper reports that by introducing an appropriate thickness of Cu spacer at a Co/Ni interface, the perpendicular magnetic anisotropy of [Co/Cu/Ni] n multilayers can be maintained at the annealing temperature as high as 400 °C, implying high post-annealing stability. X-ray reflectivity results demonstrate that the multilayers with Cu spacer exhibit good multilayer structure, indicating the weak intermixing of Co and Ni, which is one important reason for the enhanced post-annealing stability of perpendicular magnetic anisotropy. The result is of great importance for out-of-plane magnetized spintronic devices which need to be combined with complementary metal-oxide semiconductors.